2011
DOI: 10.1016/j.ejphar.2011.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rasagiline on the molecular composition of the excitatory postsynaptic density

Abstract: In the last decade, several neuroprotective therapies have been proposed for Parkinson's disease and rasagiline was indicated as one of the most promising candidates by preclinical studies. The drug has already been tested in phase III clinical studies (the ADAGIO study). The mechanism underlying rasagiline-dependent neuroprotection is complex and almost unknown. Here, we show that rasagiline is involved in the regulation of the molecular composition of the postsynaptic density of glutamatergic synapses. In hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Various molecular mechanisms appear to be associated with the neuroprotective effects of rasagiline, including upregulation of cellular antioxidant activity; induction of neurotrophic factors and neuroactive ligand receptors (Maruyama et al, 2004;Weinreb et al, 2009); prevention of the decline in mitochondrial membrane potential and nuclear translation of glyceraldehyde 3-phosphate dehydrogenase, activation of prosurvival antiapoptotic molecules (e.g., , and suppression of cell death cascades initiated by proapoptotic Bcl-2 family molecules (e.g., Bax and Bad) and caspase-3 (Akao et al, 2002b;Blandini, 2005;Maruyama et al, 2001a, Weinreb et al, 2004. Moreover, it was demonstrated that rasagiline may be involved in the regulation of the molecular composition of the excitatory postsynaptic density (Gardoni et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Various molecular mechanisms appear to be associated with the neuroprotective effects of rasagiline, including upregulation of cellular antioxidant activity; induction of neurotrophic factors and neuroactive ligand receptors (Maruyama et al, 2004;Weinreb et al, 2009); prevention of the decline in mitochondrial membrane potential and nuclear translation of glyceraldehyde 3-phosphate dehydrogenase, activation of prosurvival antiapoptotic molecules (e.g., , and suppression of cell death cascades initiated by proapoptotic Bcl-2 family molecules (e.g., Bax and Bad) and caspase-3 (Akao et al, 2002b;Blandini, 2005;Maruyama et al, 2001a, Weinreb et al, 2004. Moreover, it was demonstrated that rasagiline may be involved in the regulation of the molecular composition of the excitatory postsynaptic density (Gardoni et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…It also increases antioxidant enzyme (glutathione peroxidase and catalase) activities (Kitani et al, 2000) and inhibits mPTP opening, mitochondrial swelling and cytochrome c release (Youdim et al, n.d.;Maruyama et al, 2001;Akao et al, 2002) and caspase 3 activation (Bar-Am et al, 2005). A decrease in the synaptic density of NMDA-and AMPA receptors, responsible for initiating excitotoxicity, has also been reported with rasagiline treatment (Gardoni et al, 2011). These cellular mechanisms are considered responsible for the positive in vivo effects of rasagiline.…”
mentioning
confidence: 94%